Pengaruh Moderasi Kesadaran Anti Kecurangan dan Moralitas Pada Hubungan Sistem Pengendalian Intern Pemerintah Dengan Pencegahan Kecurangan di Balai Besar Kementerian Perindustrian Kota Bandung - Eriana Kartadjumena; Nur Indriyati (Universitas Mercu Buana Yogyakarta, 2021)
This study aims to examine the moderated effect of anti-fraud awareness and morality on the relationship between the government internal control system and fraud prevention. The study was conducted at the research institutes under the Ministry of Industry, located in Bandung. The study population involved all government employee at the research industry in Bandung. The sampling technique uses probability sampling. The research sample of 84 respondents consisting of Head of Section, Head of Section / Subdivision, Functional and staff. The data was analyzed by using the Moderating Regression Analysis (MRA) approach. The results of this study indicate that the government internal control system has a positive effect on fraud prevention, while anti-fraud awareness and morality can reduce the relationship between the government's internal control system on fraud prevention. Theoretically, the results of research can provide a reference for future research, in addition it can be used as an evaluation for work units in an effort to improve fraud prevention